Assistant Development Program for Home Industry Community at Bluru Kidul Village, Sidoarjo City - Tranggono, Didiek; Tutiasri, Ririn Puspita; Trisna Putra, Andre Yusuf (Nusantara Science and Technology Proceedings, 2020)
Maintain continuity of business needs an effective effort. However, entrepreneurs often suffer failure. Therefore, assistance from other parties is needed to provide enthusiasm and motivation support. Kelompok Usaha Bersama (KUB) Sumber Rejeki dan Kelompok Usaha Bersama (KUB) Sumber Makmur is a community group engaged in the economy in Blurukidul village, Sidoarjo district, Sidoarjo. This KUB is a forum for people of Blurukidul village to run fishery product-based businesses, such as fish smoked, fish crackers, fish meatball, and fish nugget. Clam meatball is one of the business carried out by a member of KUB. The weakness of this group is they can not carry out their business regularly and continuously. Lack of knowledge and hard capital is the main problem faced. Therefore, in the community service activity, mentoring to Kelompok Usaha Bersama (KUB) Sumber Rejeki dan Kelompok Usaha Bersama (KUB) Sumber Makmur’s member are implemented. Mentor provides motivation, determination, and hard works to achieve success in running a business. Also, community service activities are carried out by providing training on how to make clam meatballs. Participants gain knowledge and experience in producing nutritious and safe clam meatballs. The next activity was a grant of a semi-automatic meatballs printer. Using a semi-automatic meatballs printer has been proven to increase the production capacity of clam meatballs produced. The results of this activity are expected to Kelompok Usaha Bersama (KUB) Sumber Rejeki dan Kelompok Usaha Bersama (KUB) Sumber Makmur’s members are implemented increase the productivity of their business.